Pengaruh Non Performing Loan (NPL), Likuiditas, Rentabilitas, dan Efisiensi Operasional Terhadap Rasio Kecukupan Modal (Studi Kasus Pada Perbankan yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Sintia Ifadatul Aulia Fatra; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the effect of non performing loan (NPL), liquidity, profitability, and operational efficiency on the capital adequacy ratio of case studies on banks listed on the Indonesian stock exchange in 2017-2019. In this study, there are 4 (four) independent variables used to measure the capital adequacy ratio, namely non performing loans (NPL), liquidity is calculated using loan to deposit ratio (LDR), profitability which is calculated using return on assets (ROA) and operational efficiency which is calculated using operating expenses to operating income (BOPO). The dependent variable in this study is the capital adequacy ratio calculated using the capital adequacy ratio (CAR). The population in this study were all banking companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a total of 44 banking companies and the sample in this study was taken using a purposive sampling technique, namely the selection of sample members based on certain criteria and obtained a sample of 28 banking companies. The data collection method used is the documentation method by recording or documenting data listed in the annual report on (IDX). The data analysis technique used in this study is panel data regression. From this study, it resulted that the non-performing loans (NPL) had a negative and not significant effect on the capital adequacy ratio. Liquidity and profitability have a positive and not significant effect on the capital adequacy ratio. And operational efficiency has a negative and significant effect on the capital adequacy ratio.Keywords: Non Performing Loans (NPL), Liquidity, Profitability, Operational Efficiency, Capital Adequacy Ratio